Critical analysis of step‐graded polarisation engineered electron‐blocking layer optimisation for InGaN MQW laser diode. Issue 5 (1st October 2019) - Paliwal, Avinash; Singh, Kuldip; Mathew, Manish
Abstract : Here, the authors have optimised electron‐blocking layer (EBL) with step graded design for a laser diode (LD) with an emission wavelength of 450 nm. Step graded EBL contain layers of varying compositions from In0.04 Ga0.96 N to Al0.2 Ga0.8 N with the total thickness of 30 nm. The electron leakage has reduced from ∼2272 to ∼6.6 A cm −2, while hole transportation has improved by 2.185at 10 kA cm −2 injected current density. The light output power per facet of reference LD is 146.8 mW, which the authors have enhanced to 247.7 mW in authors' step‐graded EBL structure. The slope efficiency has increased by ∼61.9%. Also, the EBL energybarrier hasincreased by 324.2 meV, while the hole transportation barrierhas reduced by 77.1 meV. The reduction in hole transportation barrier and increase in EBL barrier plays the vital role in the improved performance of LDs. The built‐in potential affects the EBL band bending. Electric fields due to polarisation, ionised impurity charge distribution, and externally applied bias are investigated. It is observed that the step graded EBL structurereduces the built‐in potential at the EBL interface, thus, resulting in reduced band bending as compared to reference laser structure.